Rural/urban weight‐loss outcomes following bariatric surgery - Viviana Bauman; Andreana N. Apostolopoulos; Gwendolyn Hasse; Thomas J. Parkman; Kathryn M. Ross (Wiley, 2021)
Abstract Obesity disproportionately affects rural populations; however, there is limited research examining disparities in bariatric surgery outcomes between patients from rural versus urban areas. This study aimed to compare the demographic characteristics of patients undergoing bariatric surgery from rural versus urban bariatric areas and to explore differences in weight‐loss outcomes between these groups. A retrospective chart review identified a sample of 170 patients (52 rural, 118 urban) who underwent Roux‐en‐Y gastric bypass or vertical sleeve gastrectomy procedures over a 1‐year period. Data collected included age, race, gender, insurance status, surgery type, height, and pre‐ and postoperative weights at 3 and 6 months. Significant differences in race, ethnicity, and surgery type were observed between rural/urban patients (ps < 0.05). Patients from rural areas demonstrated significantly greater percent total weight losses at 3 months (p = 0.018; however, there were no significant differences between groups at 6 months (p > 0.05). The results suggest that patients from rural counties experience postoperative weight‐loss outcomes comparable to those of their urban counterparts.